Creating novel approaches to mitigate aflatoxin risk in food and feed with lactic acid bacteria—Mold growth inhibition and aflatoxin binding - Ahlberg, Sara H.; Joutsjoki, V.; Korhonen, H. (International Livestock Research Institute, 2014)
Aflatoxins, produced by Aspergillus fungi, are ubiquitous toxins and they can present a severe health risk to humans and animals if contaminated food and feed is consumed. Fungi live in the soil and on the surface of the crop and Aspergillus species are dominant in favorable conditions of maize cultivation areas. Climate change could threaten the production of safe food by promoting Aspergillus growth and aflatoxin production in food and feed. A novel biological approach using lactic acid bacteria (LAB) could reduce the health risks of aflatoxins through inhibiting mold growth, thus aflatoxin production and by binding existing aflatoxins. LAB are commonly used in fermented food production; they are also known to inhibit mold growth and interact with aflatoxins. LAB provide a potential novel approach to mitigate the mould growth and aflatoxin production in maize during storage and after food consumption. Mold growth inhibition by certain LAB strains may be caused by competition for resources between bacterial cells and fungi and/or production of antifungal compounds such as organic acids. Aflatoxin binding is more complex. Binding is a reversible reaction, which occurs on bacterial surfaces and involves interaction with carbohydrates, peptidoglycan and to some extent protein structures. Aflatoxin binding seems to be highly related to strain, matrix, temperature, pH, incubation time and related conditions. There are two different aspects of aflatoxin risk mitigation in this research. First is the fungal growth inhibition with LAB and second is aflatoxin binding from food and feed with LAB. We have isolated 200 strains of bacteria from 21 different indigenous fermented dairy and cereal products prepared locally in different parts of Kenya. Firstly, these strains are being tested for their growth inhibition abilities against aflatoxin producing Aspergillus fungi in laboratory conditions. Secondly, the same strains are tested for their abilities to bind and retain aflatoxin M1 and B1. Later, these same effective strains will be tested in various food and feed matrices against Aspergillus growth and then the ones with most potential will be identified. This approach aims at providing a safe method of reducing aflatoxin absorption in human gastrointestinal tract after ingesting fermented maize or dairy products, which are contaminated with aflatoxins. Novel biological methods can have a role in preventing toxic effects of aflatoxins in food and feed. Exploitation of LAB is a good option for existing methods as LAB are generally recognized as safe.